Colorblind transit planning: Modern streetcars in Washington, DC, and New Orleans. (2nd July 2020) - Brand, Anna Livia; Lowe, Kate; Hall, Em
ABSTRACT: This article analyzes case studies of the H Street Streetcar in Washington, DC, and the Rampart Streetcar in New Orleans, two newly built U.S. streetcars that are part of a national trend of modern streetcar investments. We situate these investments within state-led gentrification that exacerbates racial disparities by expanding White privilege in Black neighborhoods and reshaping racial geographies. While supporters rationalize streetcars as economic development strategies, we contextualize modern streetcars within a broader framework of colorblind neoliberalism. We advance the concept of colorblind transit planning to codify a critique of current practices and advance an argument that colorblind transit planning minimizes the ongoing salience of institutionalized racism and exacerbates existing racial geographies and experiences of race, symbolically and materially reproducing a city of exclusion. Our findings caution against further public investment in streetcars, as they contribute to state-led gentrification and private accumulation, rather than address unequal modern public transit systems.